BUSINESS MODELS OF STRATEGIC MANAGEMENT DECISIONS IN ENTREPRENEURSHIP - PANCHENKO, Volodymyr; PANCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the importance of modeling management decisions in entrepreneurship, which involves improving business processes and their effectiveness. The use of business models is proposed to be considered as a tool for forming a system of strategic management response to challenges and threats to entrepreneurial activity. It was also emphasized that the essence of the enterprise's business model should be considered through its functions. A number of priority directions for the development of entrepreneurial activity are highlighted, which are important to take into account in strategic modeling and management of business processes. A schematically modified technology of business modeling of strategic management decisions in entrepreneurship is presented, and its elements include the future priorities of consumers, existing and potential strategic resources, key competencies, the system of business processes and the business portfolio of the enterprise. The appearance of the idea of business modeling is connected with the change of the current and the emergence of new opportunities of enterprises in the market environment, and therefore with the complication of the management process. The business model should be based not only on the use of external opportunities and strengths as the basis of competitive advantages, but on the determination and development of the internal potential of the enterprise and the desire to change the parameters of the external environment in such a way that the internal potential receives maximum expression and realization. According to this, the technology of forming the business model of the enterprise is presented. In order to expand the theoretical and methodological basis for the development and implementation of strategic management solutions, the technology of forming the business model of the enterprise is schematically presented. Emphasis is placed on the importance of stable and sufficient resource provision for entrepreneurship in achieving strategic goals.
Keywords: business model; strategy; management; enterprise; business process